Attending live sporting events predicts subjective wellbeing and reduces loneliness - Helen Keyes; Sarah Gradidge; Nicola Gibson; Annelie Harvey; Shyanne Roeloffs; Magdalena Zawisza; Suzanna Forwood (Frontiers Media S.A., 2023)
IntroductionThis study explored whether attending live sporting events (LSEs) improved subjective wellbeing and loneliness, above and beyond demographic predictors.MethodsSecondary data from 7,249 adults from the Taking Part 2019-20 survey (UK household survey of participation in culture and sport) were analyzed. Multiple linear regressions captured the effect of attending LSEs (yes/no) on wellbeing variables (happiness, anxiety, a sense that life is worthwhile and life satisfaction) and loneliness, with gender, Index of Multiple Deprivation (IMD), age group, health and employment as covariates.ResultsFor life satisfaction, a sense that life is worthwhile, and loneliness, inclusion of LSE attendance in the model improved model fit significantly, although ΔR2 values were small (ΔR2 = 0.001-0.003). For happiness and anxiety, the inclusion of LSE attendance did not alter model fit. LSE attendance was associated with increased life satisfaction (b = 0.171, p < 0.001), a greater sense of life being worthwhile (b = 0.230, p < 0.001), and reduced loneliness (b = −0.083, p < 0.01).ConclusionLSE attendance has positive associations with some aspects of subjective wellbeing (life satisfaction and a sense of life being worthwhile) and loneliness, above and beyond demographic predictors. Whilst the variance explained is small, it is comparable to demographic predictors (e.g., being in employment). As even small-sized differences in SWB can have meaningful outcomes (e.g., for mortality), we conclude that LSE attendance may still offer a scalable, accessible and effective means of improving the public's wellbeing and reducing loneliness.